A rare case of unilateral postaxial duplicated foot in a developmentally normal child - Haniza, Sahdi; Hoong, Chan Wai; Ahmad Hata, Rasit; Arianto, Fredy; Siong, Lau Kiew; Nur Alyana Benjamin, Abdullah (Hong Kong Academy of Medicine Press, 2017)
Diplopodia, being a rare congenital disorder, is infrequently discussed in published texts. Most reported cases have accounted the involvement of duplicated preaxial digits with other associated organ system and physical deformities. Here, we present an unusual case of isolated diplopodia involving postaxial toes in a child with no other organ and physical abnormalities. Radiological studies revealed a set of 10-digit-duplicated foot over the lateral aspect of the native foot, complete with phalanges and its corresponding metatarsals as well as tarsals, supplied by an anomalous posterior branch of the popliteal artery. Definitive surgery was performed just before the child was learning to walk.